Audio/Video Selector 5 Channel dengan Menggunakan Program Mikrokontroler AT89C2051 - Mhd Erpandi Dalimunthe (Journal of Electrical Power Control and Automation (JEPCA), 2021)
Audio / Video Selector 5 Channel with Microcontroller AT89C2051 is a tool used to select one of the audio / video electronic equipment such as DVD player, VCD player, Playstation to be activated. This tool uses the AT89C2051 microcontroller which has been programmed as the control center of the 5 channel audio/video selector circuit by pressing the remote as the controller. The input of the device is connected to several electronic equipment and the output is connected to a television set. This tool makes it easy for owners of television sets that only have one A/V jack input.